Access to institutional credit-an economic analysis of tenant farming in east godavari district of Andhra Pradesh - Haritha Chitturi (Department of Agricultural Economics, College of Horticulture, 2012)
The formal financial system plays an important role in financing the needs of the agricultural sector in India. In order to facilitate timely and adequate credit flow to agriculture, the sector has been targeted as a part of the priority sector for the lending programmes in 1969 with an emphasis on ‘social banking’. Domestic commercial banks have been directed to allocate 18 per cent of net bank credit to agriculture and allied activities. The directed credit programme has clearly resulted in a significant increase in the amount of credit allocated to agriculture over the years. According to the Reserve Bank of India, an amount of Rs.4,76,550 crores was pumped into the agricultural sector as institutional credit as on 31-03-2012 against a target of Rs.4,75,550. However, the increased amount of agricultural credit and its outreach over the years are accompanied by several qualitative issues like timeliness, adequacy, cost and access. Inclusive financing, ie., the delivery of financial services at affordable costs to sections of disadvantaged and low income segments of the society on par with access to any public good needs more scrutiny as banks look into the total quantity of credit disbursed in a financial year only. The growing spectra of financial exclusion in agriculture, providing livelihood to more than two third of our population, particularly of small and marginal holders, and tenant farmers merit more attention in this context. The inability to offer collaterals stands between them and the institutions despite many state initiatives. The present study entitled “Access to institutional credit: An economic analysis of tenant farming in East Godavari District of Andhra Pradesh” was carried against this background with the specific objective of investigating the operational problems faced by both the tenants and bankers in credit delivery, and to suggest policy fine tuning to overcome the bottlenecks. According to the Andhra Pradesh (Andhra area) tenancy act, 1956, tenancy is permitted in the state, but it is regulated. Informal tenancy system was very prevalent in the district of East Godavari and it covered nearly 50 to 60 per cent of the cultivated area.